MARKETING OF ACADEMIC LIBRARY - Miamlina, Antonina V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article deals with the problem of promotion academic library and opportunity of motivation of the students to sign up and use books and other courses. Academic libraries can use experience of promotional library campaigns “@your library”, “use school library” and promotional materials of reading and books and also mifologems that are used in this materials.